2012
DOI: 10.1101/lm.026997.112
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the phosphodiesterase type 4 inhibitor rolipram into the amygdala at a specific time interval after learning increases recognition memory persistence

Abstract: Here we show that administration of the phosphodiesterase type 4 (PDE4) inhibitor rolipram into the basolateral complex of the amygdala (BLA) at a specific time interval after training enhances memory consolidation and induces memory persistence for novel object recognition (NOR) in rats. Intra-BLA infusion of rolipram immediately, 1.5 h, or 6 h after training had no effect on retention tested at 1, 7, and 14 d later. However, rolipram infused 3 h post-training promoted memory persistence for up to at least 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Based on recent findings (Lima et al, 2013 ) and those in Figure 3 , we suggest that dopaminergic inputs to the hippocampus are a final common point for neocortical influences on IA memory persistence driven by VTA-mPFC connections at the time of training and 12 h thereafter. The acute mPFC manipulations described here specifically affect memory persistence without altering memory formation, indicating that this cortex is part of the circuitry involved in the maintenance of the information over time together with the hippocampus and the VTA, as previously described by our groups (Bekinschtein et al, 2007 ; Rossato et al, 2009 ) and confirmed by others (Parfitt et al, 2011 , 2012 ; Werenicz et al, 2012 ).…”
Section: Discussionsupporting
confidence: 86%
“…Based on recent findings (Lima et al, 2013 ) and those in Figure 3 , we suggest that dopaminergic inputs to the hippocampus are a final common point for neocortical influences on IA memory persistence driven by VTA-mPFC connections at the time of training and 12 h thereafter. The acute mPFC manipulations described here specifically affect memory persistence without altering memory formation, indicating that this cortex is part of the circuitry involved in the maintenance of the information over time together with the hippocampus and the VTA, as previously described by our groups (Bekinschtein et al, 2007 ; Rossato et al, 2009 ) and confirmed by others (Parfitt et al, 2011 , 2012 ; Werenicz et al, 2012 ).…”
Section: Discussionsupporting
confidence: 86%
“…The animals received, via the infusion cannula, a bilateral 0.8 μl infusion of vehicle (20% dimethylsulfoxide, DMSO, in saline), the PDE4 inhibitor rolipram (7.5 μg /side dissolved in vehicle; Sigma-Aldrich, St. Louis, USA), the protein synthesis inhibitor anisomycin (80.0 μg/side dissolved in vehicle; Sigma-Aldrich, St. Louis, USA), or rolipram combined with anisomycin at the doses described above. Drug doses were chosen on the basis of previous studies (Quevedo et al, 1999; Vianna et al, 2001; Luft et al, 2006; Werenicz et al, 2012). Drug or vehicle was infused over a 30-s period.…”
Section: Methodsmentioning
confidence: 99%
“…PDE4 is widely expressed in the brain, with enrichment in reward-responsive brain regions, particularly for PDE4B (Cherry & Davis, 1999). PDE4 has been shown to participate in synaptic plasticity (Rutten et al, 2008, 2011; Wiescholleck & Manahan-Vaughan, 2012; Zhong et al, 2012) and memory, with PDE4 inhibitors utilized to enhance memories or rescue pharmacologically generated memory deficits (Werenicz et al, 2012; Zhang, Crissman, Dorairaj, Chandler, & O'Donnell, 2000; Zhang & O'Donnell, 2000; Zhang et al, 2004). PDE4 may also regulate emotional behavior, as the PDE4 inhibitor rolipram decreased depressive-like and anxiety-like behaviors in mice (Li et al, 2009).…”
Section: Phosphodiesterase Regulation Of Alcohol Intakementioning
confidence: 99%
“…PDEs are essential regulators of a variety of functions in the central nervous system, with prominent roles in synaptic plasticity (Sanderson & Sher, 2013) and learning and memory (Liddie, Anderson, Paz, & Itzhak, 2012; Roesler et al, 2014; Rutten et al, 2007; Werenicz et al, 2012). PDE inhibitors have improved cognitive deficits in rodent models of neurological dysfunction (Wang, Zhang, Zhang, & Li, 2015), including the neurodegenerative disorders Alzheimer’s, Huntington’s and Parkinson’s diseases (Fusco & Giampà, 2015) and neuropsychiatric disorders such as schizophrenia (Ramirez & Smith, 2014) and depression (Liebenberg, Harvey, Brand, & Brink, 2010; Zhang, 2009).…”
Section: Introductionmentioning
confidence: 99%